Effect of chemical composition and T6 heat treatment on the mechanical properties and fracture behaviour of Al-Si alloys for IC engine components - Vuksanović D.; Asanović V.; Šćepanović J.; Radonjić D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The microstructural examinations of Al-Si alloys intended to manufacture IC engine components revealed a complex phase composition in all the samples. The polyhedral crystals of primary silicon were detected in the Al-12.5Si alloy, besides the α-Al phase, eutectic silicon, and several intermetallic phases, identified in the cast samples of both alloys. Better tensile properties were found for the samples of Al-11Si. A predominantly intercrystalline fracture with features of ductile failure was observed in both alloys. In as-cast specimens of the Al-11Si alloy, the cracks were formed by the decohesion mechanism between the particles of the intermetallic phase AlCuFeNi and the α-Al phase. The microcracks initiated on the interface were spread along the branches of the α-Al15(Fe,Mn,Cu)3Si2 particles. After T6 treatment of the Al-11Si alloy, almost half of the intermetallics quantity presented the Al3Ni phase, while the iron-based phases were observed in a small amount. Spheroidized eutectic silicon, a smaller portion of Al5Cu2Mg8Si6, and a more considerable quantity of Al3(Fe,Mn,Cu,Ni,Co) were detected for T6 specimens of the Al-12.5Si alloy. The rounded crystals of eutectic silicon contributed to the improvement of their tensile properties. Larger and deeper dimples of mostly polygonal shapes were observed in the samples of the Al-11Si alloy after T6 treatment. The microcracks occurred at the boundary of the intermetallic phase/α-Al solid solution.